Menuju Desa Mandiri Budaya: Penguatan Promosi dan Branding Melalui Integrasi Potensi Wisata dan UMKM di Kalurahan Wirokerten - Zahra, Amila Safwah; Solihah, Sayidah Ummul; Hidayah, Dina Laelatul; Setyonugroho, Bagas; Namira, Syaakira Aulia; Zahra, Bryliant Putri; Havid, Fachrezi; Sakir, Sakir (Universitas Muhammadiyah Yogyakarta, 2025)
Wirokerten Tourism Village, located in Banguntapan District, Bantul, Yogyakarta, is a tourist destination that combines cultural richness, culinary diversity, and natural beauty with an authentic tourism concept. This study aims to analyze the role of the community in developing an independent, culture-based tourism village. The method used is Asset-Based Community Development with four stages: preparation stage, implementation stage, monitoring and evaluation, follow-up plan. The research employs a descriptive qualitative approach through literature studies, interviews, and observations to understand community involvement in tourism village management. The results indicate that the community actively participates in various aspects, such as managing Pasar Blumbang Mataram, preserving local arts and culture, providing homestays, and promoting micro, small, and medium enterprises (MSMEs). Additionally, community participation is evident in institutional development, cultural preservation, and economic activities. However, some key challenges include a lack of coordination among stakeholders and limited promotion of local products. With support from various stakeholders, Wirokerten Tourism Village has significant potential to become an independent, competitive, and sustainable tourism destination. This study highlights that the success of tourism village management depends not only on its existing potential but also on community involvement and external support. Through institutional strengthening, digital promotion, and synergy between the community, academics, and government, Wirokerten Tourism Village can develop into a leading cultural and sustainable tourism destination